Q. 274.8( 4 Votes )

# Sec4 θ –sec2θ = tan4θ + tan2θ

Answer :

Formula: -

(i) tan2θ + 1 = sec2θ

R.H.S.
tan4θ + tan2θ

Applying the formula we get,

= tan2θ [tan2θ + 1 ]

= tan2θsec2θ

= sec2θtan2θ

= sec2 θ[sec2θ – 1 ]

= Sec4θ –sec2θ

= L.H.S

R.H.S = L.H.S

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Conditional Identities31 mins
Trigonometric Functions - 0568 mins
Trigonometric Functions - 0152 mins
Graphs of trigonometric ratios | Trigonometric Identities39 mins
Quiz on Graph of Trigonometric Ratios40 mins
Trigonometric Functions - 0366 mins
Trigonometric Functions - 0658 mins
Trigonometric Series45 mins
Interactive Quiz on trigonometric ratios & identities73 mins
Trigonometric Functions - 0268 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses